Impact of neoadjuvant chemotherapy cycles on survival of patients with advanced ovarian cancer: A French national multicenter study (FRANCOGYN). (February 2020) - Lecointre, Lise; Velten, Michel; Lodi, Massimo; Saadeh, Ralph; Lavoué, Vincent; Ouldamer, Lobna; Bendifallah, Sofiane; Koskas, Martin; Bolze, Pierre Adrien; Collinet, Pierre; Canlorbe, Geoffroy; Touboul, Cyril; et al.
Abstract: Objective: The purpose of this study was to compare two groups of patients presenting advanced ovarian carcinoma benefiting from neoadjuvant chemotherapy (NAC) followed by cytoreductive surgery: after 3–4 cycles (group 1) or ≥ 5 cycles (group 2), regarding overall survival (OS) and progression-free survival (PFS), complications related to surgery as well as the extent of cytoreduction were assessed. Study design: We conducted a retrospective, multicenter cohort study in nine referral centers of France, reviewing the charts of all patients who underwent NAC between January 2000 and June 2017. We performed an OS analysis using multivariate Cox regression models adjusted for potential confounders. We also analyzed PFS and surgery-related morbidity. Results: Of 501 patients included, 236 (47.1 %) benefited from ≤ 4 NAC cycles and 265 (52.9 %) from ≥ 5 NAC cycles. Characteristics data were similar in both groups. The rate of achievement of complete surgery was similar in both groups (p = 0.28). Surgical morbidity and postoperative complications showed no significant differences between both groups. The median OS was 54.2 months, 64 months for group 1 and 49.2 months for group 2. The 5-year survival rate was 45.6 % and 27.6 %. This difference was not statistically significant [HR 1.81 (0.89–3.71), p = 0.09]. Five-year PFS was 19.7 % and 11.7 % respectively (p = 0.31). Conclusion: In a large series of advanced ovarian cancer, patients receiving late IDS (≥ 5 NAC cycles) seem to show a poorer prognosis than patients operated on earlier. The survival appears to be mainly determined by optimal resection and response to chemotherapy.